Oxidative stress during cystic ovarian disease in water buffalo - JAN, M H; DAS, G K; SINGH, J; KHAN, S; KUMAR, P; SINGH, G; SARKAR, M; PATHAK, M (The Indian Journal of Animal Sciences, 2015)
Follicular fluid and serum concentrations of antioxidants such as catalase, ascorbic acid (AA) and total antioxidant capacity (TAC) along with reactive oxygen species (ROS) and degree of oxidative damage to follicular cells, using protein carbonyl (PC) as marker of oxidative stress, were investigated during cystic ovarian disease in buffalo. Follicular fluid was aspirated from cystic follicles (>20 mm) and also from large size (10-17 mm) of cycling buffaloes. Estradiol and progesterone were estimated to determine functional status (E: P ratio) of the follicles. Cystic follicles had greater concentrations of ROS and PC and lesser concentrations of catalase, ascorbic acid and TAC than normal follicles. An interesting finding was a simultaneous decrease of TAC and increase of ROS in serum of cystic buffaloes. Results indicated a pronounced follicular fluid oxidant-antioxidant imbalance and oxidative damage to follicular proteins during cystogenesis. In conclusion, this study provided evidence about role of oxidative stress in pathogenesis of cystic ovarian disease.